Peningkatan Keterampilan Menulis Puisi Menggunakan Model Think Talk Write Siswa Kelas V SD - Hasri, Salwa Annisa; Muhammadi, Muhammadi; Taufik, Taufina (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of the study was to describe the improvement of poetry writing skills using the Think Talk Write model of fifth grade students of SDN 06 Kota Padang. The subjects of the study were 31 observers, researchers, and fifth grade students consisting of 14 men and 17 women. In the pre-writing cycle I got an average score of 73.35, the average value at writing 75.78, and the average post-writing value 75.24. In cycle II the pre-writing average score was 91.37, the average value at writing was 91.63, and the average post-writing value was 92.70. Thus writing poetry using a think talk write model can improve student learning outcomes in class V SDN 06 Kota Padang. Keywords: Poetry writing skill, think talk write